Correlates of physical activity behaviour among nursing professionals: A systematic search and literature review - Amanda H Wilkerson; Hunter O Thomas; Vinayak K Nahar (Journal of Health and Social Sciences)
Introduction: Physical activity (PA) has been shown to protect against adverse health outcomes, and factors influencing physical activity vary among different populations. Previous research suggests nurses have an increased risk of being physically inactive, which may contribute to increased risk of musculoskeletal disorders. The purpose of this investigation was to use a systematic search process to determine previously identified correlates of nurses’ physical activity. Methods: The study utilized a systematic search process to identify studies for the review. The search was performed using three electronic databases: MEDLINE, CINAHL Complete, and Web of Science. The authors extracted and synthesized information regarding physical activity levels, significant correlates of physical activity, and measures of physical activity using a narrative approach. Results: Twelve articles were included in this review. All had predominately female samples and reported statistically significant findings. The majority determined nurses’ physical activity using self-report methods (n = 11) and explored the relationship between nurses’ physical activity and individual-level variables (n = 7). Few studies explored the difference between leisure-time and work-related physical activity, and many did not assess muscle-strengthening physical activity. Discussion and Conclusions: Demographic and non-modifiable work-related factors were the most frequently assessed correlates of behaviour. The reviewed studies showed that demographic variables, such as age and BMI, were significantly associated with nursing professional’s PA. There is a need for more studies to assess factors influencing nursing professionals’ PA beyond the individual level, using theoretical designs, and including objective measures of PA. Future studies should also include assessments of nursing professionals’ muscle-strengthening PA and involve adequate representation of the United States nursing population. Practitioners and researchers working to improve nurses’ physical activity behaviour should target efforts to those more likely to engage in less physical activity, such as those with greater BMI, older age, and working night shifts, in order to tailor intervention efforts to high-risk groups.